The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/cas.14125
|View full text |Cite
|
Sign up to set email alerts
|

Uridine‐cytidine kinase 2 (UCK2): A potential diagnostic and prognostic biomarker for lung cancer

Abstract: Lung cancer has the highest morbidity and mortality among all cancers. Discovery of early diagnostic and prognostic biomarkers of lung cancer can greatly facilitate the survival rate and reduce its mortality. In our study, by analyzing Gene Expression Omnibus and Oncomine databases, we found a novel potential oncogene uridine‐cytidine kinase 2 (UCK2), which was overexpressed in lung tumor tissues compared to adjacent nontumor tissues or normal lung. Then we confirmed this finding in clinical samples. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
(36 reference statements)
1
30
0
Order By: Relevance
“…Functionally, UCK2 is a pyrimidine ribonucleotide kinase that catalyzes phosphorylation of uridine to uridine monophosphate and cytidine to cytidine monophosphate. Overexpression of UCK2 is regarded as an indicator of unfavorable prognosis in various cancers, including HCC, pancreatic cancer, breast cancer, and lung cancer ( 34 37 ). However, few studies have revealed the detailed mechanisms underlying the regulation of UCK2.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, UCK2 is a pyrimidine ribonucleotide kinase that catalyzes phosphorylation of uridine to uridine monophosphate and cytidine to cytidine monophosphate. Overexpression of UCK2 is regarded as an indicator of unfavorable prognosis in various cancers, including HCC, pancreatic cancer, breast cancer, and lung cancer ( 34 37 ). However, few studies have revealed the detailed mechanisms underlying the regulation of UCK2.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of bioinformatics methods have contributed greatly to the discovery of biomarkers associated with tumor development, diagnosis and prognosis (5)(6)(7)(8). The combined use of multiple databases of biological information for the analysis of cancer has also yielded certain breakthroughs.…”
Section: Introductionmentioning
confidence: 99%
“…Uridine-cytidine kinase 2 (UCK2) and ODF2 have not been studied in EnCa. UCK2 was proved to promote migration and invasion of hepatocellular carcinoma cells [ 41 ], which was also seen to be a latent diagnostic and prognostic indicator for lung cancer [ 42 ]. Overexpression of UCK2 was exhibited to be correlated with breast cancer progression and worse prognosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%